2020
DOI: 10.3892/ijmm.2020.4585
|View full text |Cite
|
Sign up to set email alerts
|

CircSAMD4A regulates cell progression and epithelial‑mesenchymal transition by sponging miR‑342‑3p via the regulation of FZD7 expression in osteosarcoma

Abstract: Osteosarcoma (OS) is a primary malignant tumor with a complex etiology. Therefore, research into the pathogenesis of osteosarcoma is considered a priority. circular RNAs play important roles in cell metabolism and in the immune response and are closely associated with cancer treatment. However, research into the association of circular RNAs with osteosarcoma is limited. In the present study, circSAMd4A was validated by RT-qPcR and agarose gel electrophoresis. circSAMd4A and miR-342-3p expression was detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Overexpression of FZD7 is associated with EMT in many types of cancer. In melanoma, glioblastoma, and osteosarcoma, FZD7 expression is increased and inhibition of FZD7 suppresses EMT [ 88 , 118 , 119 ]. In cervical cancer, inhibiting FZD7 reverses EMT through decreased MMP2 and MMP9 activity [ 86 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…Overexpression of FZD7 is associated with EMT in many types of cancer. In melanoma, glioblastoma, and osteosarcoma, FZD7 expression is increased and inhibition of FZD7 suppresses EMT [ 88 , 118 , 119 ]. In cervical cancer, inhibiting FZD7 reverses EMT through decreased MMP2 and MMP9 activity [ 86 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…It is a key regulator of cell growth, differentiation, invasion, and drug action, and is involved in tumor development [17]. Xie et al [18] confirmed that circSAMD4A targeted miR-342-3p via the regulation of FZD7 expression to regulate cell progression and epithelial-mesenchymal transition in osteosarcoma. Wei et al [19] proved that circSAMD4A promoted doxorubicin resistance in osteosarcoma cells by regulating the miR-218-5p/KLF8 axis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported the oncogene role of circSAMD4A in osteosarcoma. 49 Liu et al found that circSAMD4A acts as an adipogenesis promoting factor. 50 In this study, we found that hsa_circ_0002202 was up-regulated in T1DM PBMCs samples, suggesting that hsa_circ_0002202 may take part in the T1DM procession.…”
Section: Discussionmentioning
confidence: 99%